Associations of Self‐Reported History of Depression and Antidepressant Use Before Stroke Onset With Poststroke Post–Acute Rehabilitation Care—An Exploratory Study: The BASIC (Brain Attack Surveillance in Corpus Christi) Project. Issue 16 (20th August 2019) - Stulberg, Eric L.; Dong, Liming; Zheutlin, Alexander R.; Kim, Sehee; Claflin, Edward S.; Skolarus, Lesli E.; Morgenstern, Lewis B.; Lisabeth, Lynda D.
Abstract : Background: Prestroke depression status and post–acute rehabilitation care (PARC) are determinants of poststroke depression and function. However, little is known on how prestroke depression status affects PARC placement, a possible pathway for upstream intervention. We examined how prestroke depression status affects PARC in a population‐based study. Methods and Results: Incident ischemic stroke cases were from the BASIC (Brain Attack Surveillance in Corpus Christi) Project from 2008 to 2012. Prestroke depression status was self‐reported and categorized as (1) never depressed, (2) history of depression without antidepressant use before stroke onset, or (3) antidepressant use before stroke onset. PARC included home, a skilled nursing facility, or an inpatient rehabilitation facility. Confounder‐adjusted multinomial regression models were used to examine the association between prestroke depression status and PARC. Adjustment for stroke severity was deferred in the main analyses because it may lie on the causal pathway. There were 548 stroke survivors (mean age 65.3 years, 48.3% female, 62.6% Mexican‐American). The adjusted odds ratios comparing home discharge to a skilled nursing facility were 1.88 (95% CI: 0.86‐4.11) for those with a history of depression and 2.55 (95% CI: 1.11‐5.83) for those using an antidepressant at stroke onset, relative to those never depressed. The adjusted odds ratios comparing an inpatient rehabilitation facility to a skilled nursing facility were 1.17 (95% CI 0.40‐3.42) and 3.28 (95% CI 1.24‐8.67) for those with a history of depression and those using an antidepressant at stroke onset, respectively, relative to those never depressed. Conclusions: Antidepressant use before stroke onset may increase odds of home and inpatient rehabilitation facility discharge compared with skilled nursing facility discharge.